2015
DOI: 10.1590/s0100-736x2015000400005
|View full text |Cite
|
Sign up to set email alerts
|

Proteínas imunorreativas de Conidiobolus lamprauges isoladas de ovinos infectados naturalmente

Abstract: O estudo de conidiobolomicose ovina tem sido realizado nos seus aspectos clínicos, epidemiológicos, patológicos e moleculares. Informações, entretanto, sobre a resposta imune do hospedeiro na infecção por Conidiobolus lampraugessão inexistentes. Este estudo teve por objetivo a identificação de proteínas imunorreativas que possam desempenhar papel importante na resposta imune de ovinos naturalmente infectados por C. lamprauges. Para a caracterização protéica e imunológica foi utilizada a cepa de C. lamprauges(F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, treatment studies about Conidiobolus infections in sheep and goats are required. Silva et al (2015) demonstrated antigenic proteins of C. lamprauges and specific IgG in sheep sera by the immunoblot technique. The knowledge about antigenic profile against infected sheep may assist in developing early diagnostic methods and the use of protein as candidate vaccines for the control and prevention of infection.…”
Section: Discussionmentioning
confidence: 94%
“…However, treatment studies about Conidiobolus infections in sheep and goats are required. Silva et al (2015) demonstrated antigenic proteins of C. lamprauges and specific IgG in sheep sera by the immunoblot technique. The knowledge about antigenic profile against infected sheep may assist in developing early diagnostic methods and the use of protein as candidate vaccines for the control and prevention of infection.…”
Section: Discussionmentioning
confidence: 94%